Method for spectral phase retrieval of single attosecond pulses utilizing the autocorrelation of photoelectron streaking spectra - Yu, Wei-Wei; Zhao, Xi; Wei, Hui; Wang, Su-Ju; Lin, C. D. (My University, 2019)
We propose an algorithm for retrieving the spectral phase of an isolated attosecond pulse based on the photoelectron spectra generated in atoms by the attosecond pulse in the presence of a time-delayed infrared laser. Instead of employing the whole set of the streaking spectra as in the previous phase retrieval algorithms, we calculate the autocorrelation (AC) of the streaking trace, and use it to extract the spectral phase. We illustrate that this method can be used to extract narrow- as well as broadband attosecond pulses. The method converges much faster and is more accurate. We also define two parameters, V and A. By comparing the AC pattern and the V and A parameters from the experiment and from the retrieved pulse, this method provides a metric to evaluate the accuracy of the retrieved pulse.
Keywords: spectral phase retrieval; autocorrelation; photoelectron streaking spectra